TUTURAN CAMPUR KODE CINTA LAURA DAN MAUDY AYUNDA DALAM PODCAST BICARA CINTA: KAJIAN SOSIOLINGUISTIK - Fidela, Raisa; Ari Asfar, Dedy; Syahrani, Agus (IdeBahasa, 2024)
This research aims to analyze the form of code mixing used in Cinta Laura and Maudy Ayunda's speech in the "Bicara Cinta" podcast, as well as identifying the factors behind the use of code mixing using sociolinguistic studies. The method used in this research is descriptive qualitative, considering that the data analyzed is in the form of text and not numbers. The data collection technique used in this research is the observe and observe technique. The research data is in the form of dialogue excerpts in the form of words or sentences from the podcast. The data analysis technique used is qualitative discourse analysis technique. The research results show that from the 36 quotes explained, there are four forms of code mixing identified, namely: Intra-Sentential Code-Mixing, Inter-Sentential Code-Mixing, Tag-Switching, and Intra-Word Code-Mixing. Apart from that, this research also reveals several factors that influence the use of code mixing in their speech. These factors include role factors, variety factors, speaker factors, language factors, factors and the desire to explain and interpret. This research provides deeper insight into code-mixing patterns in informal communication and can be used as a reference to learn more about the use of mixed language in further contexts and different cultures.